Solvent extraction of Palladium (II) and effective separation of Palladium(II) and Platinum(IV) with synthetic sulfoxide MSO - Pan L.; Bao X.; Gu G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Extraction performances of Pd(II) and separation behaviors of Pd(II) and Pt(IV) were studied using a synthetic sulfoxide MSO as extractant from hydrochloric acid media. Pd(II) transferring was depended strongly on the MSO and HC1 concentration, phase ratio (O/A), contact time, and Pd(II) concentration in stock solution. By controlling MSO and HC1 concentration, Pd(II) and Pt(IV) could be separated effectively and the highest separation coefficient reached 758 when MSO and HC1 concentration were fixed at 25% (V/V) and 1.5 M, respectively. Pd(II) loaded in organic phase was stripped effectively with a mixed solution containing NH4C1 and ammonia solutes. The percentage stripping of Pd(II) was 95.1% using 3% (ω) NH4C1 and 3 M NH3H2O.